Endothelial dysfunction and the role of hypertension in Nepalese subjects with major coronary risk factors - Gautam, Mani Prasad; Gautam, Samir; Ghimire, Usha; Guruprasad, Sogunuru; Bhattacharya, Rabin; Subramanyam, Gangapatnam (Nepalese Heart Journal, 2016)
Background and Aims: Hypertension is one of the major coronary heart disease risk factors. Endothelial dysfunction is thought to be the preclinical vascular changes in the pathogenesis of atherosclerosis and it its major manifestation; coronary heart disease. This study was designed to assess the endothelial function in subjects with major coronary risk factors including hypertension.Methods: The study was conducted in a tertiary referral centre in Central Nepal. A cross-sectional study was conducted on the cohort of 100 subjects with at least one out of six major coronary heart disease risk factors. JNC 7 criteria were used to define hypertension. Brachial artery flow-mediated dilation was measured using high-resolution ultrasound. Endothelial dysfunction was defined as flow-mediated dilation value